PICTURES SERIES TO TEACH WRITING RECOUNT TEXT FOR TENTH GRADE OF MADRASAH ALIYAH - RISMA LESTARI; Achmad Jenwar Fitrianto; Sherly Citra Putri; Hari Prastyo; Irham Miftakhul Jannah (JETS, English Department of University of Uluwiyah Mojokerto, 2024)
This research aims to measure the effectiveness of using series of images to teach students writing skills in recount text in the tenth grade of MA Darul Ulum Ngabar Mojokerto academic year 2023/2024. The sample in this study was all 25 students of class XB, taken using a saturated sampling technique, so that the entire population could be used as a research sample in writing recount texts for tenth grade students at Madrasah Aliyah Darul Ulum Ngabar Jetis Mojokerto. Data collection in this research used pretest and posttest research instruments. The average value from the pretest was 58.48, while the average value after using images the series from the posttest was 81. Based on the results of the discussion above, it can be concluded that the picture series strategy is effective for the writing skills of class X students at MA Darul Ulum Ngabar for the 2023/2024 academic year.